Observation of the semileptonic decays B→D*τ-ν̄τ and evidence for B→Dτ-ν̄τ - Aubert, B; Bona, M; Boutigny, D; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; et al. (2008)
We present measurements of the semileptonic decays B-→D0τ- ν̄τ, B-→D*0τ-ν̄τ, B̄0→D+τ- ν̄τ, and B̄0→D*+τ-ν̄τ, which are potentially sensitive to non-standard model amplitudes. The data sample comprises 232×106 Υ(4S)→BB̄ decays collected with the BABAR detector. From a combined fit to B- and B̄0 channels, we obtain the branching fractions B(B→Dτ-ν̄τ)=(0.86±0.24±0. 11±0.06)% and B(B→D*τ-ν̄τ)=(1.62±0. 31±0.10±0.05)% (normalized for the B̄0), where the uncertainties are statistical, systematic, and normalization-mode-related. © 2008 The American Physical Society.